High-strength high-barrier PE composite packaging film and preparation method thereof
Through the modification of glass fiber and the multi-layer alternating flame retardant structure, a high-strength and high-barrier PE composite packaging film was prepared, which solved the problem of easy rupture and flammability of the packaging film, and achieved improved protection and barrier performance in a fire environment.
Patent Information
- Application Number
- CN202510642311.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-19
- Publication Date
- 2025-08-15
- Estimated Expiration
- 2045-05-19
AI Technical Summary
The existing PE composite packaging film is prone to rupture when subjected to external forces, and is flammable in fire environments, and has insufficient barrier performance and cannot effectively block the invasion of oxygen, water vapor and odor.
By modifying the surface of the glass fiber, piperazine, 3-chloropropyltriethoxysilane, methylphosphonic acid and pentaerythritol phosphate were added to form flame-retardant modified glass fibers, and the α-zirconium phosphate, chitosan and phytic acid dispersion was alternately impregnated with multiple layers to form a stable multi-layer alternating flame-retardant structure, and finally, a high-performance PE composite packaging film was prepared with polyethylene resin.
It improves the strength and flame retardant properties of the material, can delay combustion in fire situations, and effectively blocks the transmission of oxygen, water vapor and odor, enhancing the overall performance of the packaging film.
Smart Images

Figure K7VQHHFISMJNE61BWAEOYD4GKY0XB62ACBJO1M8C
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of plastic films, in particular to a high-strength and high-barrier PE composite packaging film and a preparation method thereof. Background Art
[0002] In the modern packaging sector, PE (polyethylene) composite packaging film, with its unique properties and widespread application, demonstrates significant multi-dimensional value. Firstly, PE composite packaging film's relatively low raw material costs and mature production processes allow for large-scale production, effectively reducing unit costs. This makes it highly cost-effective in the packaging market. Whether packaging food, daily necessities, or industrial products, it can achieve packaging functions at a low cost, saving companies significant packaging costs and improving economic efficiency. Secondly, its excellent processability allows for a variety of secondary processing methods, such as printing and lamination, to meet the personalized packaging needs of different products, further expanding the market and driving the development of related industries.
[0003] However, on the packaging production line, packaging films are often subjected to external forces such as stretching, squeezing, and friction, which can cause cracking or tearing. Therefore, to ensure smooth packaging, mechanical reinforcement of the packaging film is usually required. In addition, in some special storage environments or transportation scenarios, there are fire hazards. PE composite packaging films with flame retardant properties can slow down the burning speed when encountering a fire source, or even extinguish themselves, thereby reducing the possibility of fire and the speed of fire spread, providing protection for people and property. Furthermore, PE composite packaging films are often used for food packaging and pharmaceutical packaging, so their barrier properties need to be improved to effectively block the intrusion of substances such as oxygen, water vapor, and odors.
[0004] In order to overcome the defects of the prior art, the present invention provides a high-strength and high-barrier PE composite packaging film and a preparation method thereof. Summary of the Invention
[0005] The object of the present invention is to provide a high-strength and high-barrier PE composite packaging film and a preparation method thereof, so as to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a high-strength and high-barrier PE composite packaging film comprises the following steps: Step 1: Under a nitrogen environment, piperazine is added to toluene, stirred at 105-110° C. until dissolved, and then 3-chloropropyltriethoxysilane is added dropwise. After the addition is completed, the temperature is raised to 110-115° C. and refluxed for 5-6 hours. After the reaction is completed, the solvent is removed by cooling, filtering, washing, and rotary evaporation to obtain piperazinated siloxane; ethanol and deionized water are mixed uniformly, and then sodium hydroxide aqueous solution is added to adjust the solution pH to 10-11, and then the piperazinated siloxane and pretreated glass fiber are added, and the reaction is stirred at 60-70° C. for 4-5 hours. After the reaction is completed, the modified glass fiber is obtained by suction filtration, washing, and drying. The methylphosphonic acid solution is added dropwise to the modified glass fiber solution, stirred and reacted for 1.5-2.0 hours, then heated to 85-90°C and stirred and reacted for 4-5 hours, and then the pentaerythritol phosphate solution is added dropwise and stirred and reacted for 15-18 hours. After the reaction is completed, the solution is subjected to rotary evaporation, suction filtration, washing, and drying to obtain a flame-retardant modified glass fiber; Step 2: immersing the flame-retardant modified glass fiber in α-zirconium phosphate dispersion, chitosan dispersion, phytic acid dispersion, chitosan dispersion, and phytic acid dispersion in sequence for 10-15 minutes, and drying for 3-5 minutes after each immersion to obtain a flame-retardant reinforced fiber; Step 3: Mix the flame retardant reinforcing fiber and the polyethylene resin, knead them at 180-200° C. for 15-20 minutes, and then granulate them by extrusion to obtain a high-performance polyethylene resin; the high-performance polyethylene resin, polypropylene resin, adhesive, and ethylene-vinyl alcohol copolymer are sequentially compounded, film-blown, slit, and packaged to obtain a PE composite packaging film.
[0007] More optimally, in step one, the preparation process of the pretreated glass fiber is: ultrasonically washing the glass fiber for 10-15 minutes, then immersing it in a 10-15wt% hydrochloric acid solution for pretreatment for 1.5-2.0 hours, and after the pretreatment, washing, centrifuging, and drying to obtain the pretreated glass fiber.
[0008] More optimally, in step 1, the reaction molar ratio of piperazine and 3-chloropropyltriethoxysilane is (1.0-1.1):1; the reaction mass ratio of piperazinated siloxane and pretreated glass fiber is (1-2):1.
[0009] More optimally, in step 1, methylphosphonic acid is dissolved in N,N-dimethylformamide to obtain a methylphosphonic acid solution; modified glass fiber is dispersed in N,N-dimethylformamide to obtain a modified glass fiber solution; pentaerythritol phosphate is dissolved in N,N-dimethylformamide to obtain a pentaerythritol phosphate solution; wherein the reaction mass ratio of methylphosphonic acid, modified glass fiber, and pentaerythritol phosphate is (1.0-1.2):6:(1.7-2.0).
[0010] More optimally, in step 2, α-zirconium phosphate is added to deionized water, stirred evenly, and the pH is adjusted to 7.0-7.5 to obtain a 2-3wt% α-zirconium phosphate dispersion; chitosan is added to a 1.0-1.5wt% acetic acid solution, stirred evenly, and a 2-3wt% chitosan dispersion is obtained; phytic acid is added to deionized water, stirred evenly, and the pH is adjusted to 4.0-4.5 to obtain a 2-3wt% phytic acid dispersion.
[0011] More optimally, in step three, the reaction mass ratio of the flame retardant reinforcing fiber and the polyethylene resin is (1.5-1.8):5.
[0012] More optimally, in step three, the PE composite packaging film has a film layer structure from bottom to top consisting of a high-performance polyethylene-polypropylene resin layer, an adhesive layer, an ethylene-vinyl alcohol copolymer layer, an adhesive layer, and a high-performance polyethylene-polypropylene resin layer.
[0013] More optimally, the PE composite packaging film includes 45.25% high-performance polyethylene-polypropylene resin, 3% adhesive, 3.5% ethylene-vinyl alcohol copolymer, 3% adhesive, and 45.25% high-performance polyethylene-polypropylene resin; wherein the high-performance polyethylene-polypropylene resin includes 85% high-performance polyethylene resin and 15% polypropylene resin.
[0014] More optimally, in step three, the film blowing process: the head temperature of the high-performance polyethylene-polypropylene resin layer is 260-270°C, and the line speed is 100-110m / min; the head temperature of the adhesive layer is 240-250°C, and the line speed is 45-50m / min; the head temperature of the ethylene-vinyl alcohol copolymer layer is 230-240°C, and the line speed is 45-50m / min.
[0015] Beneficial effects of the present invention: The present invention is characterized in that, in step 1, a modified glass fiber is obtained by adding piperazine, 3-chloropropyltriethoxysilane, and pretreated glass fiber. This step uses a silane coupling agent to modify the pretreated glass fiber, effectively improving the dispersibility of the glass fiber and introducing a piperazine structure on the glass fiber surface. Furthermore, methylphosphonic acid is added to cause an acid-base neutralization reaction with the piperazine structure on the surface of the modified glass fiber, and then pentaerythritol phosphate is added to continue the esterification reaction with the methylphosphonic acid to produce a flame-retardant modified glass fiber.
[0016] On the one hand, both methylphosphonic acid and pentaerythritol phosphate contain phosphorus, and phosphorus-based flame retardants exhibit multiple flame-retardant mechanisms during combustion. In the initial stages of combustion, phosphorus compounds decompose upon heating to produce phosphoric acid, metaphosphoric acid, and other acidic substances. These acidic substances promote the dehydration and carbonization of organic polymers, forming a dense char layer. This char layer isolates the transfer of oxygen and heat, inhibiting further combustion. Furthermore, glass fibers act as a skeletal support within the flame-retardant system, preventing the expanded char layer from collapsing during combustion, maintaining its integrity and stability, and further enhancing the material's flame retardancy. Furthermore, glass fibers inherently possess excellent mechanical strength, and the chemical bonds and new chemical structures formed during the subsequent modification process further improve the interactions between the glass fibers, promoting better dispersion within the matrix and forming a more uniform fiber network. When the material is subjected to external forces, the individual fibers work synergistically to share the load, thereby enhancing the overall strength and toughness of the material.
[0017] The characteristics of the present invention are that, in step 2, flame retardant modified glass fiber is sequentially impregnated in α-zirconium phosphate dispersion, chitosan dispersion, phytic acid dispersion, chitosan dispersion, phytic acid dispersion to obtain flame retardant reinforced fiber. Wherein α-zirconium phosphate dispersion has negative charge characteristic, chitosan dispersion has positive charge characteristic, phytic acid dispersion has negative charge characteristic, therefore after flame retardant modified glass fiber is sequentially impregnated in a certain order, they are mutually combined by electrostatic attraction, forming a stable multi-layer alternating flame retardant structure. This stable structure is not easily destroyed during combustion, and flame retardant effect can be continuously brought into play, and each layer can be used as an independent barrier to block the transmission of heat, oxygen and combustible gas. When fiber encounters a fire source, multilayer structure can play a role step by step, effectively delaying the progress of combustion.
[0018] The present invention is characterized by mixing flame-retardant reinforcing fibers and polyethylene resin, kneading, and extrusion granulation in step three to obtain a high-performance polyethylene resin. The high-performance polyethylene resin, polypropylene resin, adhesive, and ethylene-vinyl alcohol copolymer are then sequentially compounded, film-blown, slit, and packaged to obtain a PE composite packaging film. This PE composite packaging film comprises a high-performance polyethylene resin with excellent strength and flame retardancy, and an ethylene-vinyl alcohol copolymer with excellent barrier properties, and therefore has broad application prospects in the field of plastic film technology. DETAILED DESCRIPTION
[0019] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0020] Source of raw materials: Glass fiber, particle size is 5μm; α-zirconium phosphate, provided by Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., model is α; chitosan, provided by Hebei Chuangzhiyuan Biotechnology Co., Ltd., with an active ingredient content of 99%; adhesive, provided by Mitsui of Japan, brand NF528H; ethylene-vinyl alcohol copolymer provided by Kalile of Japan, brand F104B; polyethylene resin, provided by ExxonMobil, brand 2018MA; polypropylene resin, provided by Lotte Chemical, brand PP510M.
[0021] Example 1: Step 1: The glass fiber was ultrasonically washed for 15 minutes, and then immersed in a 13 wt % hydrochloric acid solution for pretreatment for 2.0 hours. After the pretreatment, the glass fiber was washed, centrifuged, and dried to obtain a pretreated glass fiber; Under a nitrogen environment, piperazine was added to toluene, stirred at 110°C until dissolved, and then 3-chloropropyltriethoxysilane was added dropwise. After the addition was completed, the temperature was raised to 115°C and refluxed for 6 hours. After the reaction was completed, the solvent was cooled, filtered, washed, and evaporated to remove the solvent to obtain piperazinated siloxane. Ethanol and deionized water were mixed evenly, and then sodium hydroxide aqueous solution was added to adjust the solution pH to 11. Then, piperazinated siloxane and pretreated glass fiber were added, and the mixture was stirred at 70°C for 5 hours. After the reaction was completed, the mixture was filtered, washed, and dried to obtain modified glass fiber. The reaction molar ratio of piperazine to 3-chloropropyltriethoxysilane was 1.1:1; the reaction mass ratio of piperazinated siloxane to pretreated glass fiber was 1.5:1. Methylphosphonic acid is dissolved in N,N-dimethylformamide to obtain a methylphosphonic acid solution; modified glass fiber is dispersed in N,N-dimethylformamide to obtain a modified glass fiber solution; pentaerythritol phosphate is dissolved in N,N-dimethylformamide to obtain a pentaerythritol phosphate solution; the methylphosphonic acid solution is added dropwise to the modified glass fiber solution, stirred for reaction for 2.0 hours, then heated to 90° C. and stirred for reaction for 5 hours, then the pentaerythritol phosphate solution is added dropwise and stirred for reaction for 18 hours, and after the reaction is completed, the mixture is subjected to rotary evaporation, suction filtration, washing, and drying to obtain a flame-retardant modified glass fiber; wherein the reaction mass ratio of methylphosphonic acid, modified glass fiber, and pentaerythritol phosphate is 1.1:6:1.8; Step 2: Add α-zirconium phosphate to deionized water, stir evenly, and adjust the pH to 7.5 to obtain a 2.5wt% α-zirconium phosphate dispersion; add chitosan to a 1.3wt% acetic acid solution, stir evenly, and obtain a 2.5wt% chitosan dispersion; add phytic acid to deionized water, stir evenly, and adjust the pH to 4.5 to obtain a 2.5wt% phytic acid dispersion; The flame-retardant modified glass fiber was sequentially immersed in an α-zirconium phosphate dispersion, a chitosan dispersion, a phytic acid dispersion, a chitosan dispersion, and a phytic acid dispersion for 15 minutes, and dried for 5 minutes after each immersion to obtain a flame-retardant reinforced fiber; Step 3: Mix the flame retardant reinforcing fiber and the polyethylene resin, knead them at 200° C. for 20 minutes, and then granulate them by extrusion to obtain a high-performance polyethylene resin; the reaction mass ratio of the flame retardant reinforcing fiber to the polyethylene resin is 1.6:5; A PE composite packaging film is obtained by sequentially mixing, film blowing, slitting, and packaging a high-performance polyethylene resin, a polypropylene resin, an adhesive, and an ethylene-vinyl alcohol copolymer; the PE composite packaging film has a film layer structure, from bottom to top, of a high-performance polyethylene-polypropylene resin layer, an adhesive layer, an ethylene-vinyl alcohol copolymer layer, an adhesive layer, and a high-performance polyethylene-polypropylene resin layer; the PE composite packaging film comprises 45.25% of a high-performance polyethylene-polypropylene resin, 3% of an adhesive, 3.5% of an ethylene-vinyl alcohol copolymer, 3% of an adhesive, and 45.25% of a high-performance polyethylene-polypropylene resin; wherein the high-performance polyethylene-polypropylene resin comprises 85% of a high-performance polyethylene resin and 15% of a polypropylene resin; Film blowing process: The die temperature of the high-performance polyethylene-polypropylene resin layer is 270°C and the line speed is 110m / min; the die temperature of the adhesive layer is 250°C and the line speed is 50m / min; the die temperature of the ethylene-vinyl alcohol copolymer layer is 240°C and the line speed is 50m / min.
[0022] Example 2: Step 1: The glass fiber was ultrasonically washed for 13 minutes, and then immersed in a 13 wt % hydrochloric acid solution for pretreatment for 1.7 hours. After the pretreatment, the glass fiber was washed, centrifuged, and dried to obtain a pretreated glass fiber; Under a nitrogen environment, piperazine was added to toluene, stirred at 107°C until dissolved, and then 3-chloropropyltriethoxysilane was added dropwise. After the addition was completed, the temperature was raised to 112°C and refluxed for reaction for 5.5 hours. After the reaction was completed, the solvent was cooled, filtered, washed, and evaporated to remove the solvent to obtain piperazinated siloxane. Ethanol and deionized water were mixed evenly, and then sodium hydroxide aqueous solution was added to adjust the solution pH to 10.5. Then, piperazinated siloxane and pretreated glass fiber were added, and the mixture was stirred at 65°C for reaction for 4.5 hours. After the reaction was completed, the mixture was filtered, washed, and dried to obtain modified glass fiber. The reaction molar ratio of piperazine to 3-chloropropyltriethoxysilane was 1.1:1; the reaction mass ratio of piperazinated siloxane to pretreated glass fiber was 1.5:1. Methylphosphonic acid is dissolved in N,N-dimethylformamide to obtain a methylphosphonic acid solution; modified glass fiber is dispersed in N,N-dimethylformamide to obtain a modified glass fiber solution; pentaerythritol phosphate is dissolved in N,N-dimethylformamide to obtain a pentaerythritol phosphate solution; the methylphosphonic acid solution is added dropwise to the modified glass fiber solution, stirred for reaction for 1.7 hours, then heated to 87°C and stirred for reaction for 4.5 hours, then the pentaerythritol phosphate solution is added dropwise and stirred for reaction for 17 hours, and after the reaction is completed, the mixture is subjected to rotary evaporation, suction filtration, washing, and drying to obtain a flame-retardant modified glass fiber; wherein the reaction mass ratio of methylphosphonic acid, modified glass fiber, and pentaerythritol phosphate is 1.1:6:1.8; Step 2: Add α-zirconium phosphate to deionized water, stir evenly, and adjust the pH to 7.3 to obtain a 2.5wt% α-zirconium phosphate dispersion; add chitosan to a 1.3wt% acetic acid solution, stir evenly, and obtain a 2.5wt% chitosan dispersion; add phytic acid to deionized water, stir evenly, and adjust the pH to 4.2 to obtain a 2.5wt% phytic acid dispersion; The flame-retardant modified glass fiber was sequentially immersed in an α-zirconium phosphate dispersion, a chitosan dispersion, a phytic acid dispersion, a chitosan dispersion, and a phytic acid dispersion for 13 minutes, and dried for 4 minutes after each immersion to obtain a flame-retardant reinforced fiber; Step 3: Mix the flame retardant reinforcing fiber and the polyethylene resin, knead them at 190° C. for 17 minutes, and then granulate them by extrusion to obtain a high-performance polyethylene resin; the reaction mass ratio of the flame retardant reinforcing fiber to the polyethylene resin is 1.6:5; A PE composite packaging film is obtained by sequentially mixing, film blowing, slitting, and packaging a high-performance polyethylene resin, a polypropylene resin, an adhesive, and an ethylene-vinyl alcohol copolymer; the PE composite packaging film has a film layer structure, from bottom to top, of a high-performance polyethylene-polypropylene resin layer, an adhesive layer, an ethylene-vinyl alcohol copolymer layer, an adhesive layer, and a high-performance polyethylene-polypropylene resin layer; the PE composite packaging film comprises 45.25% of a high-performance polyethylene-polypropylene resin, 3% of an adhesive, 3.5% of an ethylene-vinyl alcohol copolymer, 3% of an adhesive, and 45.25% of a high-performance polyethylene-polypropylene resin; wherein the high-performance polyethylene-polypropylene resin comprises 85% of a high-performance polyethylene resin and 15% of a polypropylene resin; Film blowing process: The die temperature of the high-performance polyethylene-polypropylene resin layer is 265°C and the line speed is 105m / min; the die temperature of the adhesive layer is 245°C and the line speed is 47m / min; the die temperature of the ethylene-vinyl alcohol copolymer layer is 235°C and the line speed is 47m / min.
[0023] Example 3: Step 1: The glass fiber was ultrasonically washed for 10 minutes, and then immersed in a 13 wt % hydrochloric acid solution for pretreatment for 1.5 hours. After the pretreatment, the glass fiber was washed, centrifuged, and dried to obtain a pretreated glass fiber; Under a nitrogen environment, piperazine was added to toluene, stirred at 105°C until dissolved, and then 3-chloropropyltriethoxysilane was added dropwise. After the addition was completed, the temperature was raised to 110°C and refluxed for 5 hours. After the reaction was completed, the solution was cooled, filtered, washed, and the solvent was removed by rotary evaporation to obtain piperazinated siloxane. Ethanol and deionized water were mixed evenly, and then sodium hydroxide aqueous solution was added to adjust the solution pH to 10. Then, piperazinated siloxane and pretreated glass fiber were added, and the solution was stirred at 60°C for 4 hours. After the reaction was completed, the solution was filtered, washed, and dried to obtain modified glass fiber. The reaction molar ratio of piperazine to 3-chloropropyltriethoxysilane was 1.1:1; the reaction mass ratio of piperazinated siloxane to pretreated glass fiber was 1.5:1. Methylphosphonic acid is dissolved in N,N-dimethylformamide to obtain a methylphosphonic acid solution; modified glass fiber is dispersed in N,N-dimethylformamide to obtain a modified glass fiber solution; pentaerythritol phosphate is dissolved in N,N-dimethylformamide to obtain a pentaerythritol phosphate solution; the methylphosphonic acid solution is added dropwise to the modified glass fiber solution, stirred for reaction for 1.5 hours, then heated to 85°C and stirred for reaction for 4 hours, then the pentaerythritol phosphate solution is added dropwise and stirred for reaction for 15 hours, and after the reaction is completed, the mixture is subjected to rotary evaporation, suction filtration, washing, and drying to obtain a flame-retardant modified glass fiber; wherein the reaction mass ratio of methylphosphonic acid, modified glass fiber, and pentaerythritol phosphate is 1.1:6:1.8; Step 2: Add α-zirconium phosphate to deionized water, stir evenly, and adjust the pH to 7.0 to obtain a 2.5wt% α-zirconium phosphate dispersion; add chitosan to a 1.3wt% acetic acid solution, stir evenly, and obtain a 2.5wt% chitosan dispersion; add phytic acid to deionized water, stir evenly, and adjust the pH to 4.0 to obtain a 2.5wt% phytic acid dispersion; The flame-retardant modified glass fiber was sequentially immersed in an α-zirconium phosphate dispersion, a chitosan dispersion, a phytic acid dispersion, a chitosan dispersion, and a phytic acid dispersion for 10 minutes, and dried for 3 minutes after each immersion to obtain a flame-retardant reinforced fiber; Step 3: Mix the flame retardant reinforcing fiber and the polyethylene resin, knead them at 180° C. for 15 minutes, and then granulate them by extrusion to obtain a high-performance polyethylene resin; the reaction mass ratio of the flame retardant reinforcing fiber to the polyethylene resin is 1.6:5; A PE composite packaging film is obtained by sequentially mixing, film blowing, slitting, and packaging a high-performance polyethylene resin, a polypropylene resin, an adhesive, and an ethylene-vinyl alcohol copolymer; the PE composite packaging film has a film layer structure, from bottom to top, of a high-performance polyethylene-polypropylene resin layer, an adhesive layer, an ethylene-vinyl alcohol copolymer layer, an adhesive layer, and a high-performance polyethylene-polypropylene resin layer; the PE composite packaging film comprises 45.25% of a high-performance polyethylene-polypropylene resin, 3% of an adhesive, 3.5% of an ethylene-vinyl alcohol copolymer, 3% of an adhesive, and 45.25% of a high-performance polyethylene-polypropylene resin; wherein the high-performance polyethylene-polypropylene resin comprises 85% of a high-performance polyethylene resin and 15% of a polypropylene resin; Film blowing process: The die temperature of the high-performance polyethylene-polypropylene resin layer is 260°C and the line speed is 100m / min; the die temperature of the adhesive layer is 240°C and the line speed is 45m / min; the die temperature of the ethylene-vinyl alcohol copolymer layer is 230°C and the line speed is 45m / min.
[0024] Comparative Example 1: omitting step 2, and the rest being the same as Example 1, the specific steps are as follows: Step 1: ultrasonically washing the glass fiber for 15 minutes, and then immersing it in a 13wt% hydrochloric acid solution for pretreatment for 2.0 hours. After the pretreatment, washing, centrifuging, and drying are performed to obtain pretreated glass fiber; Under a nitrogen environment, piperazine was added to toluene, stirred at 110°C until dissolved, and then 3-chloropropyltriethoxysilane was added dropwise. After the addition was completed, the temperature was raised to 115°C and refluxed for 6 hours. After the reaction was completed, the solvent was cooled, filtered, washed, and evaporated to remove the solvent to obtain piperazinated siloxane. Ethanol and deionized water were mixed evenly, and then sodium hydroxide aqueous solution was added to adjust the solution pH to 11. Then, piperazinated siloxane and pretreated glass fiber were added, and the mixture was stirred at 70°C for 5 hours. After the reaction was completed, the mixture was filtered, washed, and dried to obtain modified glass fiber. The reaction molar ratio of piperazine to 3-chloropropyltriethoxysilane was 1.1:1; the reaction mass ratio of piperazinated siloxane to pretreated glass fiber was 1.5:1. Methylphosphonic acid is dissolved in N,N-dimethylformamide to obtain a methylphosphonic acid solution; modified glass fiber is dispersed in N,N-dimethylformamide to obtain a modified glass fiber solution; pentaerythritol phosphate is dissolved in N,N-dimethylformamide to obtain a pentaerythritol phosphate solution; the methylphosphonic acid solution is added dropwise to the modified glass fiber solution, stirred for reaction for 2.0 hours, then heated to 90° C. and stirred for reaction for 5 hours, then the pentaerythritol phosphate solution is added dropwise and stirred for reaction for 18 hours, and after the reaction is completed, the mixture is subjected to rotary evaporation, suction filtration, washing, and drying to obtain a flame-retardant modified glass fiber; wherein the reaction mass ratio of methylphosphonic acid, modified glass fiber, and pentaerythritol phosphate is 1.1:6:1.8; Step 2: Mixing the flame retardant modified glass fiber and polyethylene resin, kneading at 200° C. for 20 minutes, and then extruding and granulating to obtain high-performance polyethylene resin; the reaction mass ratio of the flame retardant modified glass fiber to the polyethylene resin is 1.6:5; A PE composite packaging film is obtained by sequentially mixing, film blowing, slitting, and packaging a high-performance polyethylene resin, a polypropylene resin, an adhesive, and an ethylene-vinyl alcohol copolymer; the PE composite packaging film has a film layer structure, from bottom to top, of a high-performance polyethylene-polypropylene resin layer, an adhesive layer, an ethylene-vinyl alcohol copolymer layer, an adhesive layer, and a high-performance polyethylene-polypropylene resin layer; the PE composite packaging film comprises 45.25% of a high-performance polyethylene-polypropylene resin, 3% of an adhesive, 3.5% of an ethylene-vinyl alcohol copolymer, 3% of an adhesive, and 45.25% of a high-performance polyethylene-polypropylene resin; wherein the high-performance polyethylene-polypropylene resin comprises 85% of a high-performance polyethylene resin and 15% of a polypropylene resin; Film blowing process: The die temperature of the high-performance polyethylene-polypropylene resin layer is 270°C and the line speed is 110m / min; the die temperature of the adhesive layer is 250°C and the line speed is 50m / min; the die temperature of the ethylene-vinyl alcohol copolymer layer is 240°C and the line speed is 50m / min.
[0025] Comparative Example 2: Steps 1 and 2 are omitted, and the rest are the same as in Example 1. The specific steps are as follows: Step 1: glass fiber and polyethylene resin are mixed, kneaded at 200° C. for 20 minutes, and then extruded and granulated to obtain high-performance polyethylene resin; the reaction mass ratio of glass fiber to polyethylene resin is 1.6:5; A PE composite packaging film is obtained by sequentially mixing, film blowing, slitting, and packaging a high-performance polyethylene resin, a polypropylene resin, an adhesive, and an ethylene-vinyl alcohol copolymer; the PE composite packaging film has a film layer structure, from bottom to top, of a high-performance polyethylene-polypropylene resin layer, an adhesive layer, an ethylene-vinyl alcohol copolymer layer, an adhesive layer, and a high-performance polyethylene-polypropylene resin layer; the PE composite packaging film comprises 45.25% of a high-performance polyethylene-polypropylene resin, 3% of an adhesive, 3.5% of an ethylene-vinyl alcohol copolymer, 3% of an adhesive, and 45.25% of a high-performance polyethylene-polypropylene resin; wherein the high-performance polyethylene-polypropylene resin comprises 85% of a high-performance polyethylene resin and 15% of a polypropylene resin; Film blowing process: The die temperature of the high-performance polyethylene-polypropylene resin layer is 270°C and the line speed is 110m / min; the die temperature of the adhesive layer is 250°C and the line speed is 50m / min; the die temperature of the ethylene-vinyl alcohol copolymer layer is 240°C and the line speed is 50m / min.
[0026] Comparative Example 3: The preparation of the flame-retardant reinforcing fiber is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: A polyethylene resin, a polypropylene resin, an adhesive, and an ethylene-vinyl alcohol copolymer are sequentially compounded, film-blown, slit, and packaged to obtain a PE composite packaging film; the PE composite packaging film has a film layer structure from bottom to top of a polyethylene resin + polypropylene resin layer, an adhesive layer, an ethylene-vinyl alcohol copolymer layer, an adhesive layer, and a polyethylene resin + polypropylene resin layer; the PE composite packaging film comprises 45.25% polyethylene resin + polypropylene resin, 3% adhesive, 3.5% ethylene-vinyl alcohol copolymer, 3% adhesive, and 45.25% polyethylene resin + polypropylene resin; wherein the polyethylene resin + polypropylene resin comprises 85% polyethylene resin and 15% polypropylene resin; Film blowing process: The die temperature of the polyethylene resin + polypropylene resin layer is 270°C and the line speed is 110m / min; the die temperature of the adhesive layer is 250°C and the line speed is 50m / min; the die temperature of the ethylene-vinyl alcohol copolymer layer is 240°C and the line speed is 50m / min.
[0027] Detection test: Mechanical property test: Referring to GB / T1040.3 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets", the PE composite packaging film prepared in the present invention was cut into specimens with a size of 170×20×0.5 mm. The tensile strength was tested using a universal tensile testing machine with a tensile rate set at 20 mm / min.
[0028] Flame retardant performance test: Referring to GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method - Part 2: Room temperature test", the PE composite packaging film prepared in the present invention was cut into samples with a size of 120×50×0.5 mm, and the oxygen index value was measured and recorded using an oxygen index meter.
[0029] Barrier performance test: Referring to GB / T 1038-2000 "Plastic Film and Sheeting Gas Permeability Test Method - Pressure Differential Method", the PE composite packaging film prepared in this invention was used as a sample to test the oxygen transmission rate. The results are shown in the following table: Conclusion: The dosages used in Examples 1 to 3 remained unchanged, and only some reaction parameters were modified. The experimental data show that there was no significant fluctuation in the performance of the samples.
[0030] Comparative Example 1: Step 2 is removed, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the tensile strength is reduced to 85.7 MPa, and the oxygen index is reduced to 25.2%. The reason is analyzed as follows: in step 2, the glass fiber is modified by adding flame retardants such as piperazine, 3-chloropropyltriethoxysilane, methylphosphonic acid, and pentaerythritol phosphate to obtain a flame retardant modified glass fiber; therefore, the flame retardant modified glass fiber has good flame retardant properties and mechanical strength. Therefore, after removing it, the tensile strength is reduced and the oxygen index is reduced.
[0031] Comparative Example 2: Steps 1 and 2 were removed, and the rest was the same as in Example 1. From the experimental data, it can be seen that compared with Example 1, the tensile strength was reduced to 83.3 MPa, and the oxygen index was reduced to 21.3%. The reason for this was that Comparative Example 2 further removed the multi-layer alternating flame retardant structure on the basis of Comparative Example 1, so the flame retardant performance was further reduced, and the oxygen index was reduced to 21.3%.
[0032] Comparative Example 3: The preparation of flame-retardant reinforcing fiber is removed, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the tensile strength is reduced to 76.7 MPa and the oxygen index is reduced to 20.8%. The reason for this is that Comparative Example 3 further removes the reinforcing glass fiber on the basis of Comparative Example 2, so the mechanical properties of the sample are reduced, and the tensile strength is reduced by 76.7 MPa.
[0033] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "include," "comprise," or any other variations thereof are intended to encompass non-exclusive inclusion, such that a process, method, article, or apparatus comprising a series of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.
[0034] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art will be able to modify the technical solutions described in the aforementioned embodiments or substitute equivalents for some of the technical features. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.
Claims
1. A method for preparing a high-strength and high-barrier PE composite packaging film, characterized in that: The following steps are involved: Step 1: Under a nitrogen environment, piperazine is added to toluene, stirred at 105-110° C. until dissolved, and then 3-chloropropyltriethoxysilane is added dropwise. After the addition is completed, the temperature is raised to 110-115° C. and refluxed for 5-6 hours. After the reaction is completed, the solvent is removed by cooling, filtering, washing, and rotary evaporation to obtain piperazinated siloxane; ethanol and deionized water are mixed uniformly, and then sodium hydroxide aqueous solution is added to adjust the solution pH to 10-11, and then the piperazinated siloxane and pretreated glass fiber are added, and the reaction is stirred at 60-70° C. for 4-5 hours. After the reaction is completed, the modified glass fiber is obtained by suction filtration, washing, and drying. The methylphosphonic acid solution is added dropwise to the modified glass fiber solution, stirred and reacted for 1.5-2.0 hours, then heated to 85-90°C and stirred and reacted for 4-5 hours, and then the pentaerythritol phosphate solution is added dropwise and stirred and reacted for 15-18 hours. After the reaction is completed, the solution is subjected to rotary evaporation, suction filtration, washing, and drying to obtain a flame-retardant modified glass fiber; Step 2: immersing the flame-retardant modified glass fiber in α-zirconium phosphate dispersion, chitosan dispersion, phytic acid dispersion, chitosan dispersion, and phytic acid dispersion in sequence for 10-15 minutes, and drying for 3-5 minutes after each immersion to obtain a flame-retardant reinforced fiber; Step 3: Mix the flame retardant reinforcing fiber and the polyethylene resin, knead them at 180-200° C. for 15-20 minutes, and then granulate them by extrusion to obtain a high-performance polyethylene resin; the high-performance polyethylene resin, polypropylene resin, adhesive, and ethylene-vinyl alcohol copolymer are sequentially compounded, film-blown, slit, and packaged to obtain a PE composite packaging film.
2. The method for preparing a high-strength and high-barrier PE composite packaging film according to claim 1, characterized in that: In step 1, the preparation process of pretreated glass fiber is as follows: the glass fiber is ultrasonically washed with water for 10-15 minutes, and then immersed in a 10-15wt% hydrochloric acid solution for pretreatment for 1.5-2.0 hours. After the pretreatment, it is washed with water, centrifuged, and dried to obtain pretreated glass fiber.
3. The method for preparing a high-strength and high-barrier PE composite packaging film according to claim 1, characterized in that: In step 1, the reaction molar ratio of piperazine to 3-chloropropyltriethoxysilane is (1.0-1.1):1; the reaction mass ratio of piperazinated siloxane to pretreated glass fiber is (1-2):
1.
4. The method for preparing a high-strength and high-barrier PE composite packaging film according to claim 1, characterized in that: In step 1, methylphosphonic acid is dissolved in N,N-dimethylformamide to obtain a methylphosphonic acid solution; modified glass fiber is dispersed in N,N-dimethylformamide to obtain a modified glass fiber solution; pentaerythritol phosphate is dissolved in N,N-dimethylformamide to obtain a pentaerythritol phosphate solution; wherein the reaction mass ratio of methylphosphonic acid, modified glass fiber, and pentaerythritol phosphate is (1.0-1.2):6:(1.7-2.0).
5. The method for preparing a high-strength and high-barrier PE composite packaging film according to claim 1, characterized in that: In step 2, α-zirconium phosphate is added to deionized water, stirred evenly, and the pH is adjusted to 7.0-7.5 to obtain a 2-3wt% α-zirconium phosphate dispersion; chitosan is added to a 1.0-1.5wt% acetic acid solution, stirred evenly, and a 2-3wt% chitosan dispersion is obtained; phytic acid is added to deionized water, stirred evenly, and the pH is adjusted to 4.0-4.5 to obtain a 2-3wt% phytic acid dispersion.
6. The method for preparing a high-strength and high-barrier PE composite packaging film according to claim 1, characterized in that: In step 3, the reaction mass ratio of the flame retardant reinforcing fiber and the polyethylene resin is (1.5-1.8):
5.
7. The method for preparing a high-strength and high-barrier PE composite packaging film according to claim 1, characterized in that: In step three, the PE composite packaging film has a film layer structure from bottom to top consisting of a high-performance polyethylene-polypropylene resin layer, an adhesive layer, an ethylene-vinyl alcohol copolymer layer, an adhesive layer, and a high-performance polyethylene-polypropylene resin layer.
8. The method for preparing a high-strength and high-barrier PE composite packaging film according to claim 7, characterized in that: The PE composite packaging film includes 45.25% high-performance polyethylene-polypropylene resin, 3% adhesive, 3.5% ethylene-vinyl alcohol copolymer, 3% adhesive, and 45.25% high-performance polyethylene-polypropylene resin; wherein the high-performance polyethylene-polypropylene resin includes 85% high-performance polyethylene resin and 15% polypropylene resin.
9. The method for preparing a high-strength and high-barrier PE composite packaging film according to claim 1, characterized in that: In step three, the film blowing process: the head temperature of the high-performance polyethylene-polypropylene resin layer is 260-270°C, and the line speed is 100-110m / min; the head temperature of the adhesive layer is 240-250°C, and the line speed is 45-50m / min; the head temperature of the ethylene-vinyl alcohol copolymer layer is 230-240°C, and the line speed is 45-50m / min.
10. A high-strength and high-barrier PE composite packaging film, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.